Effect of Natural Disasters on Tourism Development in Kabale District: A case Study of Lake Bunyonyi. - Rubahamya, Ian (Kabale University, 2024)
The study was about assessing the impact of Natural Disasters on Tourism Development in Kabale District. A case study of Lake Bunyonyi. The study was guided by three objectives which were: to determine the effects of natural disasters on tourism development in the Kabale district, to find out the challenges hindering tourism development as a result of natural disasters, to suggest possible measures to solve the challenges hindering tourism development as results natural disaster. The targeted population was 103 respondents who were considered for the study. These included local communities, NGOs, local government, tourists, and CBOs. Both simple random and purposive sampling techniques in identifying the study sample population. The methods that were used in data collection included surveys, observations, and interviews. Data collected was edited, coded, entered into the computer, and analyzed with Excel, a Microsoft statistical package, the results were presented in tables. According to the findings, 100% of the respondents agreed that there were the effects of natural disasters on tourism development in the Kabale district and these included injuries, deaths, chronic Disease Emergencies, cancelations of bookings, shortages of food, mental health problems, damage to Infrastructure, floods, hygienic impacts and the spread of disease. The study revealed the challenges hindering tourism development as a result of natural disasters and these included limited tourism infrastructure, perception of safety and security, limited tourist offerings, natural disaster vulnerability, socio-economic challenges, lack of awareness and promotion, and limited air connectivity. From objective three, the study indicated the possible measures to solve the challenges hindering tourism development as a result of natural disasters and these included improving the quality and quantity of attractions, having a risk management process in place, providing maps and directions to local events and attractions, create an email list to share information about your destination, promote local events and businesses, share tourism events and attractions on social media.